Are the Lessons from the Financial Crisis on Using Modern Finance Theory as the Intellectual Framework for Financial Regulation Reflected in Post-crisis Regulation? - Conor Duffin-Hall (UCL Journal of Law and Jurisprudence, 2019)
To download this paper please click https://discovery.ucl.ac.uk/id/eprint/10086917/ Modern finance theory informed the approach to financial regulation before the financial crisis. However, the crisis exposed the inadequacy of using modern finance theory as the intellectual framework for financial regulation, providing important lessons for future reform. Since the crisis, regulators and policymakers have been seeking to strengthen the financial system to avoid a repeat of 2008. Therefore, it is apposite to ask whether regulators and policymakers are simply taking the same, flawed pre-crisis approach and using modern finance theory as the basis for financial regulation, or whether there has been a fundamental pivot in their approach. This article examines how modern finance theory informed the pre-crisis regulatory approach, how doing so contributed to the failure of the financial system and examines two examples of post-crisis regulation to understand how, and whether, the lessons from the financial crisis are being incorporated into regulators’ and policymakers’ post-crisis approach to financial regulation.